PENGTINGNYA PARTISIPASI WALI MURID DALAM MENINGKATKAN MINAT BELAJAR SISWA - Atnawi Atnawi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
Things that have little role and meaning in this education problem are the roles and participation of parents in the family. As one part of the educational institution that has the first and foremost predicate, families should be a good opportunity to catch up with children in school or can also be used as additional momentum to understand and clarify material from school. Thus the role of parents in this problem is very large. As part or component of the education system, guardians of students and the community in general are entitled to develop their participation in the advancement of education. In the development of children's learning interest and many are influenced by several by several factors, both internal and external factors. Participation of guardian students is included in the external section which has important values in efforts to increase children's learning interest. The participation of guardian students can be useful in increasing students' interest in learning, this can be seen from the emergence of encouragement of children to study hard, easy and easy for students to solve the difficulties they face and as a medium for success in learning.